The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/pin.12706
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multidisciplinary strategies and traditional approaches in teaching pathology in medical students

Abstract: This study aims to evaluate the impact on the implementation of multiple strategies to improve medical student's pathology learning experience. In two consecutive years, medical students after a whole year of enrolling in pathology teaching, were invited to complete questionnaires rating and commenting on the personal learning experience of multiple teaching resources delivered in pathology. In both years, the overall score was high (mean score = 4.57 ± 0.63 /5) for the newly introduced sessions, namely histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…[7] One study that assessed multiple pathology teaching methods found that online modules integrated with virtual microscopy and clinical cases were very useful for learning and positively received by medical students. [8] However, neither study had a concurrent control group as in our study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…[7] One study that assessed multiple pathology teaching methods found that online modules integrated with virtual microscopy and clinical cases were very useful for learning and positively received by medical students. [8] However, neither study had a concurrent control group as in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Our pilot study expands on similar studies that demonstrated the benefits of online modules and virtual microscopy for medical education. [781214] The advantages of online resources include convenience, accessibility, interactivity, and individualized learning. A meta-analysis showed that internet-based learning is associated with positive outcomes compared to no intervention and is as effective as traditional teaching methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the advent of whole slide imaging (WSI), the utility of digitized slides for education in medical school and residency has been amply documented. Entire histology and histopathology databases exist on digital platforms,[123] “unknown” slides are routinely made available to residents for review prior to conferences,[1] many major academic medical centers have made thematic slide collections digitally available for medical student[456] and resident[789] education, and continuing medical education seminars in pathology are frequently hosted on digital platforms. These applications have enhanced the educational value of histologic and pathologic slides by affording use that is unrestricted in time or place and by preventing loss of educational slide sets through breakage, misplacement, and theft.…”
Section: Introductionmentioning
confidence: 99%
“…Digital microscopy through whole-slide imaging (WSI) has been used in training programs of pathology residents and as a component of education for undergraduate students in several medical-related schools, mainly in histology and pathology subjects. [23456789101112] WSI is also used in histopathological routine diagnosis, substituting conventional microscopy. [131415] The images are stored in high resolution and samples can be manipulated, similarly to conventional light microscopy.…”
Section: Introductionmentioning
confidence: 99%